Sex workers working within a legalised industry: their side of the story. Issue 5 (12th June 2008) - Groves, J; Newton, D C; Chen, M Y; Hocking, J; Bradshaw, C S; Fairley, C K
Abstract : Objectives: To examine the characteristics and work attitudes of female sex workers working in licensed brothels in Victoria, Australia. Methods: This was a cross-sectional study of sex workers working at 38 of the 92 licensed brothels operating in Victoria during 2006. Results: Of the 108 women approached, 97 (90%) completed the questionnaire. Women working in the legal sex industry in Victoria were generally aged between 23 and 35 years (51%), had completed high school (26%) and had worked in the industry for more than 5 years (43%). Half had dependent children and one third were in a relationship. Women's primary motivation for working in the sex industry was financial, whether this was the reason for their starting (56%), or the barrier to their leaving (61%). Although women valued the higher income and flexibility of this work, many were concerned about sexually transmitted infections (STI) (55%), community attitudes towards the industry (47%), their physical safety (38%) and maintaining their anonymity (37%). Over half of the women would like to leave the industry. The majority (95%) supported the monthly STI checks that are part of the Victorian regulations, with only one fifth reporting that the cost of these tests was prohibitive. Conclusions: The findings of this study indicate that women working in licensed Victorian brothels come from a diverse range of backgrounds and circumstances and hold varying attitudes towards working in the sex industry. It is hoped that these findings go some way to redressing the assumptions commonly made about women working in the sex industry and reducing the stigma associated with this occupation.